2019
DOI: 10.1017/s1431927619014636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanomechanical Properties of Tomato Root by Atomic Force Microscopy

Abstract: Here, different tissue surfaces of tomato root were characterized employing atomic force microscopy on day 7 and day 21 of growth through Young's modulus and plasticity index. These parameters provide quantitative information regarding the mechanical behavior of the tomato root under fresh conditions in different locations of the cross-section of root [cell surface of the epidermis, parenchyma (Pa), and vascular bundles (Vb)]. The results show that the mechanical parameters depend on the indented region, tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This observation can be attributed to the contact area between the lateral root and substrate, which is much larger than that between the taproot and substrate [35]. Models (7)(8) revealed that as the seedling substrate's moisture content increased, the lateral root tissue's maximum stress and strain decreased. This observation is because the moisture content of the seedling substrate was closely related to the mechanical properties of the substrate.…”
Section: Sensitivity To the Seedling Agementioning
confidence: 99%
See 1 more Smart Citation
“…This observation can be attributed to the contact area between the lateral root and substrate, which is much larger than that between the taproot and substrate [35]. Models (7)(8) revealed that as the seedling substrate's moisture content increased, the lateral root tissue's maximum stress and strain decreased. This observation is because the moisture content of the seedling substrate was closely related to the mechanical properties of the substrate.…”
Section: Sensitivity To the Seedling Agementioning
confidence: 99%
“…The existing literature on plant root mechanics mainly focuses on the root's cell hardness and elastoplastic mechanical characterization. Nicolás-Álvarez et al [6,7] found that the elastic modulus of epidermal cells of tomato seedling roots increased from 9.19 ± 0.68 to 13.90 ± 1.68 MPa while the elastic modulus of parenchyma cells and vascular bundle cells decreased from 1.74 ± 0.49 and 10.60 ± 0.58 to 0.48 ± 0.55 and 6.37 ± 0.53 MPa, respectively from day 7 to day 21. Fernandes et al [8] discovered that the inherent surface mechanical properties of living Arabidopsis thaliana whole-root epidermal cells showed nanoscale heterogeneity.…”
Section: Introductionmentioning
confidence: 99%